(untitled) (diségno, 2025)
Since its first edition in 2015, hosted by the Universitat Politècnica de València (Spain), the international FORTMED conference –dedicated to the study of Mediterranean fortifications– has established itself as a key annual event for the academic and scientific community. [read more]